In search of the lost polychromy of English medieval alabaster panels in the Southwest of France. Issue 3 (5th February 2020) - Mounier, Aurelie; Schlicht, Markus; Mulliez, Maud; Pacanowski, Romain; Lucat, Antoine; Mora, Pascal
Summary: Polychrome alabaster carvings, representing religious scenes, constitute England's major contribution to European mediaeval sculpture. During the period between 1350 and 1550, large number of alabaster carvings were produced in the Midlands. Despite their massive destruction during the English Reformation (ca.1534), more than 2500 of them still survive, either legally exported or sold clandestinely to the Continent. With more than 100 panels still existing, the Bordeaux region holds one of the largest concentrations of these reliefs. Most of them have unfortunately lost their medieval polychromy, but 20 can still provide valuable information. They are currently studied in our multidisciplinary research program "ALBATRES" (Polychromie, pigments, perception: les albâtres anglais de la fin du Moyen Âge conservés sur le territoire aquitain. Labex LaScArBx project [2018‐2020]). Focused on the panels' polychromy, the project links art history, archaeometry, optical and 3D engineering, and experimental archeology. The first aim is to obtain complete information on the materials and techniques used by medieval painters. The second consists in studying the functions of polychromy and its perception, by determining and interpreting the selection criteria and aesthetic uses of colors and gilding. The polychrome remains of the Aquitaine corpus are studied by means of visual examination, macrophotographic documentation, and noninvasive portable spectroscopic analyses (reflectance spectroscopy by fiber optics in visible and infrared ranges, fluorimetry, etc.). They reveal, among others, the presence of cinnabar, red lead, red ochre, copper green pigments, yellow ochre, gold, lead white, and others. The results allow the production of model samples to help understand the medieval color organization before proposing the coloring of a real copy of one of the studied panels (Virgin's Assumption, Musée d'Aquitaine, Bordeaux). The shape and the appearance of the color rendering could be improved thanks to a special device built at the IOGS to develop a shader that approximates as closely as possible the appearance of the panels. Finally, all information will be integrated on 3D model panels for better appreciation of the carvings and the artistic taste of medieval spectators.